Avaliação dos desfechos clínicos com uso da terapia antimicrobiana: Polimixina B - Pacheco, Liliane Souto (2014)
This study aims at evaluating the clinical outcomes with the use of Polymyxin B, antibiotic that is being increasingly used across the current needs of antimicrobial therapy. Was developed in the 40s for the treatment of gram-negative bacilli, and fell into disuse because of its toxicity, mainly renal. Despite this increased use is poorly understood its true efficacy and its toxicity profile (ZAVASCKI et al., 2010, p.71). Among the clinical outcomes analyzed the mortality at 30 days and the occurrence of acute kidney injury (AKI). This evaluation was made by means of a retrospective cohort study, based on data collection from medical records of adult patients admitted to the University Hospital of Santa Maria (HUSM), who received Polymyxin B for more than 48 hours. For evaluation of the nephrotoxicity RIFLE criteria were used. The diagnosis of infection was made according to the criteria of the National Health Surveillance Agency (Anvisa). We evaluated 53 patients, mean age 56 years, 29 (55%) men and 24 (45%) women. AKI occurred in 25 (53%) participants, with an average start of 8.5 (± 4.9) days. In thirty days, 12 (48%) patients showed improvement of renal function to pretreatment levels. Doses above 25 mg / kg / day and previous normal renal function, doses were positively correlated with worsening kidney. Regarding the clinical outcome observed that 29 (55%) had a favorable outcome at 14 days. Eighteen (34%) participants died within 30 days after initiation of treatment. As risk factors for death were found combined use with other active drug to BGN resistant to carbapenems (p-value 0.028, RR 13 CI 1.3 to 130), and SOFA score greater than eight (p-value <0.029, RR 1.3 CI 15 to 179). The conclusion is based on these findings, the mortality related to use of Polymyxin B is dependent on the degree of comorbidities presented by the patient (SOFA) and the use or not of combination therapy. This last finding may be due to a bias of severity of infection. When it was found that nephrotoxicity is an agent with nephrotoxic potential, and that the occurrence of AKI is influenced by the prescribed daily dosage. The fact of the LRA have been more frequent in patients without renal injury corroborates the hypothesis that greater care with other causative factors for AKI may decrease its occurrence in patients using polymyxin B.